Os determinantes do custo do voto: uma análise para a eleição de 2010 - Silva, Clarissa Benatti (2013)
Several studies support the idea that electoral campaign costs play a decisive role on the election results. It is common in Brazil the use of pork barreling (works aimed at the public and resources that are used as clientelistic tools by politicians). The objective of this work is to analyze if the vote cost varies among important regions, states, meso regions and micro regions and if those variations are affected by social-economic features. This study uses the constant information from the TSE´s repository as its database as well as social-economic indexes from Brazilian meso and micro regions. The analyses were carried out for the candidates to state and federal representatives in the e 2010 elections. The results from the nonparametric tests show that Brazilian elections cannot be analyzed by considering the whole country because the vote costs means are statistically different among large regions and states. By the Spearman´s correlation coefficient it is concluded that those differences are not related to the electoral quotient. This study also concludes, by the log-linear regressions, that votes are more expensive in poorer micro regions, that is, the larger the economic inequalities in the region, the higher the value the candidate must spend to obtain votes.